A digital community archive as an object of discourse studies. Prolegomena - Ciesek-Ślizowska, Bernadetta; Duda, Beata; Ficek, Ewa; Przyklenk, Joanna; Sujkowska-Sobisz, Katarzyna (Papers in Linguistics, 2022)
The article first presents the phenomenon that is described today as the digital community archive. The overview of the discussed study object (cognitively interesting but so far still overlooked in the linguistic or discourse-oriented considerations on individual or common memory, memory culture, memory discourses, etc.) was preceded by some definition conclusions presented here. The researchers supplemented this overview with: 1. description of the socio-cultural background of the contemporary archival sources; 2. presentation of the research background, including the research assumptions and description methods; 3. assessment of possibilities and limitations connected with exploring the outlined field of study and indicating in this field the most important research problems, i.e.: subjects’ identities that can be seen in digital community archives; axiological and ideological aspects of the images of the past that are re/constructed by the participants of the community archive area; the subject plane and discursive image of the world; private and/vs. public discourse considering the community archives, and – in a broader sense – the position of the archive in the contemporary sphere of communication. The authors believe that the archive should receive more attention from the discourse researchers mainly due to its vital social role played not only in the humanities, but also in the contemporary participatory thinking (civic and community-generating).